Cultural Dynamics and Gender Diversity : A Deep Dive into Women in Leadership Roles - Zapf, Lisa-Marie (2024)
This thesis critically examines the barriers to women's leadership in Central and Eastern Europe, particularly exploring the complex interplay of gender biases, cultural influences, and organizational practices. Despite comprising a significant portion of the workforce, women remain underrepresented in leadership roles, primarily due to persistent gender stereotypes and cultural disparities that hinder their career progression. Utilizing a qualitative research design, this study delves into the personal narratives of 20 women leaders across various multinational corporations in Austria, Czech Republic, Germany, Hungary, and Poland. Conducted through in-depth interviews via Microsoft Teams from January to February 2024, the research captures a broad spectrum of experiences and perspectives, offering insights into both the systemic barriers and individual challenges faced by women. The findings reveal that gender biases and the dual burden of career and caregiving responsibilities significantly impact women’s opportunities for advancement. Additionally, the study discusses the effectiveness of existing policies such as gender quotas and flexible work arrangements, while also proposing further initiatives to enhance gender diversity in leadership. By highlighting these challenges and offering evidence-based recommendations, this thesis contributes to the discourse on gender equality, advocating for organizational changes that support women’s ascent in leadership hierarchies.